This Is Marketing: You Can't Be Seen Until You Learn to See - Seth Godin (Penguin Business, 2018)
Over the past quarter century, Seth Godin has taught and inspired millions of entrepreneurs, marketers, leaders, and fans from all walks of life, via his blog, online courses, lectures, and bestselling books. He is the inventor of countless ideas and phrases that have made their way into mainstream business language, from Permission Marketing to Purple Cow to Tribes to The Dip. Now, for the first time, Godin offers the core of his marketing wisdom in one accessible, timeless package. At the heart of his approach is a big idea: Great marketers don't use consumers to solve their company's problem; they use marketing to solve other people's problems. They don't just make noise; they make the world better. Truly powerful marketing is grounded in empathy, generosity, and emotional labour. This book teaches you how to identify your smallest viable audience; draw on the right signals and signs to position your offering; build trust and permission with your target market; speak to the narratives your audience tells themselves about status, affiliation, and dominance; spot opportunities to create and release tension; and give people the tools to achieve their goals. It's time for marketers to stop lying, spamming, and feeling guilty about their work. It's time to stop confusing social media metrics with true connections. It's time to stop wasting money on stolen attention that won't pay off in the long run. This is Marketing offers a better approach that will still apply for decades to come, no matter how the tactics of marketing continue to evolve.
Keywords: Business; Leadership; Nonfiction; Self Help